The influence of physical strain on esophageal motility in healthy volunteers studied with gas‐perfusion manometry. Issue 8 (24th May 2015) - Hoehne, S.; Schneider, A.; Hesse, V.; Brosig, U.; Finke, R.
Abstract Background The influence of physical strain on the esophageal motility has already been examined in a number of studies. It was found that high physical strain compromises the sufficient contractility of the esophagus. However, it needs more examinations to verify these findings. Methods To validate these results healthy volunteers were examined using gas‐perfusion manometrie. Bicycle ergometry was performed to generate an exactly defined physical exercise. After a pilot study, the changing of the contraction amplitude was determined as the main variable to evaluate the esophageal motility, and the sample size was calculated. Eight subjects without esophageal diseases or symptoms were examined by simultaneous gas‐perfusion esophageal manometry and bicycle ergometry. Key Results The results showed that high physical strain during bicycle ergometry can induce a significant decrease of the contraction amplitude (α = 5%, β = 10%). The 95% confidence interval of the quotient of contraction amplitude at rest and under physical strain is (1.074; 1.576). This effect is more pronounced in liquid acts of swallowing than in dry and is also more obvious at the middle measuring point (7.8 cm above the lower esophageal sphincter) than at the distal and proximal point (2.8 and 12.8 cm). Furthermore, a decreasing tendency of the contraction duration could be found. Conclusions & Interferences Gas‐perfusion manometry is an inexpensive examination method, which enables the evaluation of the esophageal motility in moving test subjects under conditions of physical strain. It could be proved that physical strain negatively influences the esophageal motility by a decrease of the contraction amplitude.